Predicted stable high-pressure phases of copper-nitrogen compounds. (28th October 2021) - Zhou, Yuting; Jiang, Xingxing; Zheng, Yueshao; Xie, Sheng-Yi; Feng, Yexin; Chen, Keqiu
Abstract: The nitrogen-rich compounds are promising candidates for high-energy-density applications, owing to the large difference in the bonding energy between triple and single/double nitrogen bonds. The exploration of stable copper–nitrogen (Cu–N) compounds with high-energy-density has been challenging for a long time. Recently, through a combination of high temperatures and pressures, a new copper diazenide compound ( P 63 / mmc -CuN2 ) has been synthesized (Binns et al 2019 J. Phys. Chem. Lett. 10 1109–1114). But the pressure-composition phase diagram of Cu–N compounds at different temperatures is still highly unclear. Here, by combining first-principles calculations with crystal structure prediction method, the Cu–N compounds with different stoichiometric ratios were searched within the pressure range of 0–150 GPa. Four Cu–N compounds are predicted to be thermodynamically stable at high pressures, Pnnm -CuN2, two CuN3 compounds with the P -1 space group (named as I-CuN3 and II-CuN3 ) and P 21 / m -CuN5 containing cyclo-N5 − . Finite temperature effects (vibrational energies) play a key role in stabilizing experimentally synthesized P 63 / mmc -CuN2 at ∼55 GPa, compared to our predicted Pnnm -CuN2 . These new Cu–N compounds show great promise for potential applications as high-energy-density materials with the energy densities of 1.57–2.74 kJ g −1 .